An analysis of online reviews by language groups: The case of hotels in Porto, Portugal. - Pacheco, Luís Miguel (2016)
Electronic word-of-mouth has gained importance with the emergence of new online tools and the hospitality sector is at the core of that phenomenon. In this paper we employ a secondary data set of hotel guest reviews for Porto, Portugal, star-rated hotels on a large online travel platform, to explore the distribution and difference in rating behavior of English, Portuguese, Spanish, French and Brazilian guests in an online environment. We find that hotels should promote greater participation by customers in online review platforms, since the average review rating tends to increase with the number of reviews. In terms of language groups, we find that Brazilian travelers tend to give higher ratings and that Spanish travelers are at the other end of the spectrum. Also, low-class hotels are more likely to have customer satisfaction differences, whereas upgrading from a four to a five-star hotel yields a slight boost in ratings. Our results point out that special attention should be given to Spanish guests in all hotel classes, but particularly in middle and low-class hotels. These hotels should be more attentive towards their Spanish guests, exerting more effort to satisfy them in order to obtain better online ratings.